A time of sifting mystical marriage and the crisis of Moravian piety in the eighteenth century - Peucker, Paul 1963- (Penn State Univ. Press, 2015)
"Examines the eighteenth-century crisis in the Moravian Church known as the Sifting Time, and the church's subsequent shift from radical beliefs and practices to conservative mainstream Protestantism"...Provided by publisher
Includes bibliographical references and index
Keywords: Zinzendorf, Nikolaus Ludwig von -- 1700-1760; Moravian Church -- History -- 18th century; Geschichte 1700-1800; Geschichte; Religion; Piety -- History -- 18th century; Marriage -- Religious aspects -- Moravian Church -- History -- 18th century; Pietismus; Böhmische Brüder; Brüdergemeine; Religiöser Wandel